Modern Methods of Construction Design Proceedings of ICMD 2013 - Sevcik, Ladislav; Lepsik, Petr; Petru, Michal; Masin, Ivan; Martonka, Rudolf (Lecture Notes in Mechanical Engineering,, 2014)
This book has been created on the basis of contributions to the 54th International Conference of Machine Design Departments, that was held for the 60th anniversary of Technical University of Liberec. This international conference which follows a tradition going back more than 50 years, is one of the longest-running series of conferences held in central Europe, dealing with methods and applications in machine design. The main aim of the conference was to provide an international forum where experts, researchers, engineers and industrial practitioners, managers and Ph.D. students could meet, share their experiences and present the results of their efforts in the broad field of machine design and related fields. The book has seven chapters which focus on new knowledge of machine design, optimization, tribology, experimental methods and measuring, engineering analyses and product innovation. Authors presented new design methods of machine parts and more complex assemblies with the help of numerical methods such as FEM. Research, measurements and studies of new materials, including composites for energy-efficient constructions are also described. The book also includes solutions and results useful for optimization and innovation of complex design problems in various industries. .